2018
DOI: 10.1051/matecconf/201819904002
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding corrosion initiation in concrete – influence of local concrete properties in the steel-concrete interfacial zone

Abstract: Chloride-induced corrosion is the most common deterioration process for reinforced infrastructure objects. Improving the understanding of the conditions for initiation of localized corrosion is urgently needed. Research is focused on the influence of “defects” at the steel-concrete interface (SCI), as these weak points might be responsible for corrosion initiation. In contrast to numerous studies with “lab concrete”, this study reports results from reinforced concrete cores drilled from old infrastructure obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This statement is also confirmed by Glass et al [10], who observed that the chloride threshold value for corrosion initiation of steel increases if the percentage of air voids at the SCI decreases. However, recent studies reported that defects at the SCI did not have any influence on corrosion initiation under certain environmental conditions [11,12]. Angst et al [4] observed by visual inspection that the location of corrosion onset did not coincide with the location of interfacial air voids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement is also confirmed by Glass et al [10], who observed that the chloride threshold value for corrosion initiation of steel increases if the percentage of air voids at the SCI decreases. However, recent studies reported that defects at the SCI did not have any influence on corrosion initiation under certain environmental conditions [11,12]. Angst et al [4] observed by visual inspection that the location of corrosion onset did not coincide with the location of interfacial air voids.…”
Section: Introductionmentioning
confidence: 99%
“…So, the lack of electrolyte at these locations could prevent corrosion to initiate. Boschmann et al [12] found that corrosion initiation in the majority of cases did not occur at air voids in cores taken from existing structures, that were exposed in the laboratory to chloride solution. Although several studies have been conducted on the influence of interfacial defects for corrosion initiation [4][5][6][7][8][9][10][11][12][13], on-going research on the topic highlights the importance to clarify if, and how, interfacial voids may affect the chloride critical value and so initiation of corrosion.…”
Section: Introductionmentioning
confidence: 99%